Characterization and comparison of performance of students with learning difficulties and good readers from public and private school in tests of reading and writing of words and pseudowords - Capellini, Simone Aparecida [UNESP]; Germano, Giseli Donadon [UNESP] (My University, 2015)
Reading and writing are complex activities composed of multiple interdependent processes. The recognition and the production of written words in an alphabetic writing system, can occur through a direct visual process (lexical route) or by a process involving phonological mediation (phonological route) as the models of reading and writing Dual -Route. This study aim to characterize and compare the performance of students with Learning Difficulties (LD) and good readers from public and private schools in tests of reading and writing of words and nonwords. A total of 160 students from 2nd to 5th grades level (80 students from public school and 80 from private school) participated of this study, and they were submit to a Tests of Reading and Writing of words and nonwords. As results of this study, we could observe that there was several difference in the performance of students of public and private school when we look through out grade level, the presence or absence of learning difficulties and effect of regularities and frequency of words.
Keywords: assessment; education; learning; reading; writing